Fishery Policy Framework and Policy Capacity Gaps in Nepal (Journal of the Bangladesh Agricultural University, 2025)
The fishery sector in Nepal contributes NPR. 13 billion to the economy and employs over 500,000 people. Current fish production in Nepal as 5.7 t/ha/year, with potential production significantly higher at 10 t/ha/year, presenting tremendous growth opportunities. This paper assesses the capacity of policy actors to formulate, formalize, implement, and evaluate fishery policies. Based on the current fishery policy framework, this paper brings qualitative information collected through literature review, field observations, interviews, stakeholder consultation meetings, key informant interviews (KIIs), and focus group discussions (FGDs). The findings revealed significant gaps in the policy process, framework, and the capacity of policy actors. Moreover, it highlights deficiencies in institutional capabilities, the availability and use of reliable data and evidence for policy. Additionally, the paper identifies the fact about poor coordination among relevant ministries; existing lack of coherence with associated acts and policies, and issues with feed and nutrition, marketing, investment, and loan provisions that mainly hinder the promotion of the fishery sector herefore, fostering stronger linkages and collaborative efforts across all levels of government is essential to address existing policy gaps and unluck the full potential of Nepalese fisheries.J Bangladesh Agril Univ 23(2): 250-258, 2025